Effects of Special Therapeutic Footwear on the Prevention of Diabetic Foot Ulcers: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (26th September 2022) - Luo, Bo; Cai, Yuying; Chen, Dawei; Wang, Chun; Huang, Hui; Chen, Lihong; Gao, Yun; Ran, Xingwu
Abstract : Objective . To reduce diabetic foot ulcer (DFU) occurrence or recurrence, diabetic therapeutic footwear is widely recommended in clinical practice for at-risk patients. However, the effectiveness of therapeutic footwear is controversial. Thus, we performed a systematic review and meta-analysis of randomized controlled trials (RCTs) to examine whether special therapeutic footwear could reduce the incidence of DFU. Method . We systematically searched multiple electronic databases (Medline, EMBASE, and EMB databases) to identify eligible studies published from inception to June 11, 2021. The database search, quality assessment, and data extraction were independently performed by two reviewers. Efficacy (i.e., incidence of DFU) was explored using the R'meta' package (version 4.15-1). To obtain more robust results, the random-effects model and the Hartung-Knapp-Sidik-Jonkman method were selected to assess pooled data. Metaregression analysis and sensitivity analysis were performed to explore heterogeneity, and publication bias was assessed by a visual inspection of funnel plots and the AS-Thompson test. Results . Eight RCTs with a total of 1, 587 participants were identified from the search strategy. Compared with conventional footwear, special therapeutic footwear significantly reduced the incidence of DFU (RR 0.49; 95% CI, 0.28-0.84), with no evidence of publication bias (P = 0.69 ). Unexpectedly, the effectiveness of special therapeutic footwear had a reverse correlation with the intervention time (coefficient = 0.085, P < 0.05 ) in the metaregression analysis. Conclusion . Special therapeutic footwear with offloading properties is effective in reducing the incidence of DFU. However, the effect may decrease gradually over time. Despite undefined reasons, the optimal utility time and renewal frequency of special therapeutic footwear should be considered.